2013
DOI: 10.1007/s10059-013-0260-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel In Vitro Culture Condition Improves the Stemness of Human Dermal Stem/Progenitor Cells

Abstract: Cell therapy using adult stem cells has emerged as a potentially new approach for the treatment of various diseases. Therefore, it is an essential procedure to maintain the stemness of adult stem cells for clinical treatment. We previously reported that human dermal stem/progenitor cells (hDSPCs) can be enriched using collagen type IV. However, hDSPCs gradually lose their stem cell properties as in vitro passages continue. In the present study, we developed optimized in vitro culture condition to improve the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…NHDFs were plated onto collagen type IV-coated dishes and then sorted on the basis of their ability to adhere to collagen type IV within 5 min (hDSPCs) or within 12 hr (non hDSPCs) at 37°C [11,19,20].…”
Section: Cell Culture and Enrichment Of Hdspcsmentioning
confidence: 99%
See 1 more Smart Citation
“…NHDFs were plated onto collagen type IV-coated dishes and then sorted on the basis of their ability to adhere to collagen type IV within 5 min (hDSPCs) or within 12 hr (non hDSPCs) at 37°C [11,19,20].…”
Section: Cell Culture and Enrichment Of Hdspcsmentioning
confidence: 99%
“…Compared to normal human dermal fibroblasts (NHDFs), hDSPCs have relatively high proliferative properties and show higher expression levels of dermal stem cell markers such as SOX2 and S100β. They can also differentiate into mesodermal cell types (adipocytes, chondrocytes, and osteoblasts) and neuronal lineage under specific culture conditions [19,20]. Furthermore, the CM of hDSPCs can recover the expression levels of NHDFs specific markers such as collagen, MMP1 and TIMP1 in UVA-irradiated NHDFs.…”
Section: Introductionmentioning
confidence: 96%
“…DPCs have been intensively investigated to possess many advantages for cell therapy approaches. However, many studies also demonstrated the loss of their stemness and inductive activity during the in vitro passages [ 4 , 6 – 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the proliferation and differentiation of stem cells are controlled depending on the media. 14,33,34 Human corneal endothelial cells have been reported not to proliferate in vivo, 2,3 although HCECs proliferate in vitro. Therefore, these results suggest that medium B and medium BE could provide a similar environment to that found in vivo for HCECs.…”
Section: Figmentioning
confidence: 98%